Peningkatan Kemampuan Penalaran Matematika Berbasis Pisa Melalui Metode Problem Solving (PTK pada Siswa Kelas VIII A2 Semester Ganjil MTs Negeri Surakarta II Tahun 2015/2016) - KUSUMOWATI, HENDRATI YUNI (2016)
Hendrati Yuni Kusumowati/ A410110126 REASONING ABILITY IMPROVEMENT THROUGH PISA BASED MATH PROBLEM SOLVING METHOD (PTK in Class VIII A2 MTs Negeri Surakarta Odd Semester II Year 2015/2016). Essay. The Faculty of Education, University of Muhammadiyah Surakarta. Januari, 2016. The purpose of this research to describe an increase in the PISA mathematical reasoning based A2 class VIII MTs Negeri Surakarta II with methods of problem solving. This study uses a classroom action research. Source data comes from teachers and students. Implementation of a class action carried out for three cycles with 3 meeting. Methods of data collection is done through tests, observations, field notes, interview and documentation. Data analysis technique used qualitative descriptive through three stages of data reduction, exposure data, and inference. Validity of data with triangulation of methods and sources. Results of the first study, the application of problem solving methods can improve PISA mathematical reasoning based A2 class VIII MTs Negeri Surakarta II. Secondly, the increase in mathematical reasoning that is : 1) submitted allegations initial condition as much as 6 students (21.43%), The first cycle to 9 students (32.14%), the second cycle to 13 students (46.43%), after the third cycle of action to increase to 19 students (67.86%), 2) perform mathematical manipulations initial conditions for 3 students (10.71%), Cycle I counted 5 students (17.86%), the second cycle to 8 students (28.57%), then after the third cycle of action to increase to 14 students (50%), 3) draw conclusions, compile evidence, giving reasons or evidence of the truth of the solution initial conditions as much as 5 students (17.86%), the first cycle of 7 students (25%), the second cycle increased to 11 students (39.29%), and after the third cycle of action to increase to 17 students (60.71%). Keywords: mathematics learning, mathematical reasoning, PISA, problem solving